A two-phased approach for the centralisation versus decentralisation of the hospital sterilisation service department. (3rd March 2009) - Tlahig, Houda; Jebali, Aida; Bouchriha, Hanen
This paper introduces an iterative two-phased approach to decide on the centralisation versus decentralisation of the hospital sterilisation service department. The first step consists in searching for the optimum configuration that minimises the sterilisation activity cost, while the second step consists in finding the adequate dimensioning of that optimum configuration. The motivation of this study is embedded on the practical needs of Tunisian hospitals. The developed approach is based on two mathematical programming models. [Received 27 May 2008; Revised 4 October 2008; Accepted 27 November 2008]